2015
DOI: 10.1016/j.vetmic.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of equine rotaviruses isolated in Europe in 2013: Implications for vaccination

Abstract: Equine group A rotavirus (RVAs) mainly cause disease in foals under the age of 3 months. Only sporadic data are available on the circulation of RVAs in equine populations in Europe. In this study, 65 diarrheic samples from foals under 4 months of age were collected in Belgium (n=32), Germany (n=17), Slovenia (n=5), Sweden (n=4), Hungary (n=3), Italy (n=2), France (n=1) and The Netherlands (n=1). Forty percent of these samples (n=26) were found to be RVA positive by a quantitative RT-PCR assay. The viral load i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
13
0
2
Order By: Relevance
“…The Ct values obtained by the in-house rtRT-PCR assay were 21 and 18.3, compared to 26.18 and 36.01, respectively, by the commercial rtRT-PCR kit. While we did not have additional equine samples to further examine this, these high Ct values from equine samples are consistent with a previous report (Matthijnssens et al, 2015) in which the same commercial molecular assay was also used for diarrheic samples from equine. Ct values for positive samples from that study ranged from 26.18-36.01.…”
Section: Discussionsupporting
confidence: 88%
“…The Ct values obtained by the in-house rtRT-PCR assay were 21 and 18.3, compared to 26.18 and 36.01, respectively, by the commercial rtRT-PCR kit. While we did not have additional equine samples to further examine this, these high Ct values from equine samples are consistent with a previous report (Matthijnssens et al, 2015) in which the same commercial molecular assay was also used for diarrheic samples from equine. Ct values for positive samples from that study ranged from 26.18-36.01.…”
Section: Discussionsupporting
confidence: 88%
“…Group A rotaviruses are a primary cause of diarrhea in children and animal species, including horses [1-6, 43, 44]. Even though seven G-types and six P-types of ERVA have been identified in horses, the G3P [12] and G14P [12] constitute the most epidemiologically relevant genotypes [1,2,[17][18][19]. Spatial as well as temporal fluctuations between these predominant G-types (G3 and G14) of ERVA circulating in equine populations have been reported around the world [2,30].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 27 G-types and 35 P-types of RVA have been recognized in several species including humans [9]. Thus far, seven G-types (G3, G5, G6, G8, G10, G13 and G14) and six P-types (P [1], P [3], P [7], P [11], P [12] and P [18]) have been identified among the RVA affecting horses, with G3P [12] and G14P [12] being the most prevalent and epidemiologically relevant genotypes [1,2,[17][18][19]. Other genomic arrangements involving G-and P-types different from G3/G14 and P [12] have been infrequently described as infecting horses [1].…”
Section: Introductionmentioning
confidence: 99%
“…Based on differences within RVA, a number of genotypes have been described for the VP4 (P[1]-P[37]), VP6 (I1-I16) and VP7 (G1-G27) gene (Estes & Greenberg, 2013;Matthijnssens et al, 2012;Trojnar et al, 2013 (Browning et al, 1991;Ciarlet et al, 2001;Isa et al, 1996;Miño et al, 2013;Taniguchi et al, 1994), G3P[12] and G14P[12] are the most prevalent strains associated with diarrhoea in foals worldwide. Rotavirus strains carrying the G3 genotype have been found in a wide range of host species (Estes & Greenberg, 2013;Martella et al, 2010), but the equine-like G3, G14 and P[12] genotypes have never been found producing outbreaks in any other host species than equines (Bailey et al, 2013;Garaicoechea et al, 2011;Matthijnssens et al, 2015;Weinberg et al, 2013). Genomes of equine RVA G3P [12] and G14P[12] are highly conserved, and only three gene segments have shown different genotypes (i.e.…”
Section: Introductionmentioning
confidence: 99%